A Review of Prevention and Adjuvant Therapy in Acute Respiratory Syndrome Caused by COVID-19 from the Perspective of Persian Medicine - M Azimi (Babol University of Medical Sciences, 2021)
BACKGROUND AND OBJECTIVE: COVID-19 started in December 2019 in Wuhan, China and quickly became a global pandemic. According to studies, traditional medicine interventions along with conventional medicine protocols have been reported to be effective in prevention and treatment. The aim of this study was to summarize the recommendations of Persian medicine based on evidence in the prevention and treatment of symptoms of acute respiratory syndrome. METHODS: In this review article, keywords related to the symptoms of COVID-19 in Persian medicine sources, review and items related to the prevention and treatment of acute respiratory syndrome were extracted. Individual items with the keywords "Influenza" or "SARS" or "MERS" or "COVID-19" or "Coronavirus" or "Antiviral" or "Anti-inflammatory" or "Immune system" or "Antioxidant" were searched in the databases SID, Pubmed, Scopus, Cochrane, Web of science, Science direct, and Google scholar, and finally those with scientific evidence were presented in the form of auxiliary instructions for prevention and treatment. FINDINGS: A significant part of the recommendations of Persian medicine to prevent or control the symptoms of acute respiratory syndrome has practical clinical evidence. These include social distance, avoiding heavy meals, and using herbal remedies according to the specific conditions of the patients. CONCLUSION: According to the results of this study, the use of simple strategies of Persian medicine in preventing and improving the symptoms of acute respiratory syndrome caused by COVID-19 along with common medicine protocols, can help control the epidemic conditions. Also, many of these recommendations can be evaluated as useful research ideas in the prevention and treatment of COVID-19.